Robotlar - Stewart, Melissa; Dinç, Derya (Ankara : National Geographic : Beta Kids, 2015)
Introduces robots and the science behind these amazing machines, including a historic timeline of robot development, common jobs robots perform in the workplace and at home, and robots of the future.
Includes index.
3-6.
Turkish.
Keywords: Robots -- Juvenile literature; Robots